Application of Problem Based Learning Model with SETS Vision to Increase Students' Learning Motivation on Environmental Pollution Material - Yusrizal Yusrizal; Zarlaida Fitri; Hafnati Rahmatan; Ibnu Khaldun; Fatimahwati Fatimahwati (Jurnal Penelitian Pendidikan IPA, 2021)
This study aims to determine the increase in learning motivation and student responses to the application of the Problem Based Learning model with SETS vision on environmental pollution material at SMP Negeri 8 Banda Aceh. This research is a quantitative study using an experimental research design in the form of a nonequivalent control group design. The number of students in this study was 40 students consisting of 20 students in class VII-5 as the experimental class and 20 students in class VII-7 as the control class. Data were collected through a motivation questionnaire and a response questionnaire. Data analysis was carried out quantitatively. The results showed that the implementation of the PBL model with SETS vision can increase students' learning motivation on environmental pollution material. The average learning motivation of experimental class students increased by 30 with an N-Gain score of 0.74 which is in the high category. The positive response of students is higher than the negative response to the application of the Problem Based Learning (PBL) model with SETS vision on environmental pollution material. The average response of students is greater than 81 which is in very good criteria